Raw Genotype Data for "Unravelling Admixture, Inbreeding and Recent Selection Signatures in West-African Indigenous Cattle Populations in Benin" - Vanvanhossou, Sèyi Fridaïus Ulrich; Justus Liebig University Giessen (My University, 2021)
The data presented here are genotype data generated and exploited for different analyses in our study entitled "Unravelling Admixture, Inbreeding and Recent Selection Signatures in West-African Indigenous Cattle Populations in Benin" The folders are organized from 1. to 4. following the order in which the data were generated (from our own data to the extended datasets). In each folder, a README file provides an extensive description of the dataset, the number of variants and animals, the breeds, the statistical analyses and further references.
Sèyi Fridaïus Ulrich Vanvanhossou
Keywords: ddc:630